Financial System Management for Increasing the Potential of Bicak Village BUMDes - Tatas Ridho Nugroho; Puji Handayati; Kukuh Budianto; Mifta Ria Oktaviana; Nabila Aura Dewanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
BUMDes is one of the Indonesian government’s programs to advance the welfare of rural communities through the management of local economic potential and the provision of services at the village level. However, there are still obstacles, namely, the financial management of BUMDes, which is not yet optimal due to the lack of understanding of managers regarding the preparation of systematic financial reports. The purpose of this service, as well as training and mentoring, is to increase the knowledge and ability of BUMDes management regarding the importance of correct, transparent, and accountable financial reports according to SAK-ETAP or SAK EMKM. This community service aims to encourage an increase in BUMDes business potential and profit through improving its financial management system. This activity consists of several stages, which include preparation or planning stage, survey and problem identification, problem solving, implementation, and evaluation of activities. The approach taken to resolve issues with partners and provide solutions was to conduct training and mentoring, introducing techniques for preparing financial reports using Microsoft Excel and providing comprehensive guidance to the public on Standard Operating Procedures (SOP). This activity comprises training and guidance, introducing financial reporting techniques using Microsoft Excel, and providing comprehensive understanding of Standard Operating Procedures (SOP) to the community. The results of this community service activity demonstrate that the participants were able to comprehend and utilize Microsoft Excel to prepare financial reports for the BUMDes. This was evidenced by the responses given during the discussion session and the ability to apply Excel formulas to process financial data during the training and mentoring sessions.